Illuminated and Decorated Medieval Manuscripts in the University Library, Utrecht : An Illustrated Catalogue - Horst, K. van der (European History and Culture - Book Archive pre-2000., 1989)
Of all the illuminated and decorated manuscripts in the UL-Utrecht, all miniatures with identifiable subjects are illustrated and indexed, along with a choice of the minor decorations. Over 65 manuscripts are illuminated in Utrecht, the most important centre of book production in the Netherlands during the late Middle Ages.